2011
DOI: 10.1136/heartjnl-2011-300198.128
|View full text |Cite
|
Sign up to set email alerts
|

128 Bright blood t2 weighted MRI has higher diagnostic precision and accuracy than dark blood stir MRI for assessment of the ischaemic area-at-risk and myocardial salvage in acute myocardial infarction

Abstract: (NICE) have released guidelines for the investigation of chest pain of recent onset (1). There is concern that the guidelines will increase the burden on cardiac imaging, requiring service reconfiguration and investment (2, 3). This study was performed to assess the impact of the guidelines on outpatient cardiology services in the UK. Methods 595 consecutive patients attending chest pain clinics at two hospitals over six months preceding release of the NICE guidelines (51% male; median age 55 yrs (range 22e94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…Our semiquantitative scoring showed fairly similar values for the extent of myocardial edema as assessed by T2 mapping and the extent of myocardial infarction as assessed by LGE. However, from previous studies it could have been expected that the T2 map edema score would be higher than the LGE score, since it has been shown that the edema zone is larger than the LGE zone in AMI [22,28,29]. However, the conflict between our findings and this expectation is only contrived.…”
Section: Herz 169contrasting
confidence: 56%
See 2 more Smart Citations
“…Our semiquantitative scoring showed fairly similar values for the extent of myocardial edema as assessed by T2 mapping and the extent of myocardial infarction as assessed by LGE. However, from previous studies it could have been expected that the T2 map edema score would be higher than the LGE score, since it has been shown that the edema zone is larger than the LGE zone in AMI [22,28,29]. However, the conflict between our findings and this expectation is only contrived.…”
Section: Herz 169contrasting
confidence: 56%
“…In a recently published study Payne et al assessed the diagnostic performance of T2w dark-blood TSE for the detection of myocardial edema in AMI on a coronary artery perfusion territory basis. They found that T2w dark-blood TSE showed myocardial edema within the perfusion territory of the culprit coronary artery only in 61 % of cases [22]. Even though T2 mapping showed better sensitivity than T2w dark-blood TSE imaging, the sensitivity of T2 mapping is not perfect.…”
Section: Herz 169mentioning
confidence: 99%
See 1 more Smart Citation
“…CMR scans were performed on a Siemens MAGNETOM Avanto (Erlangen, Germany) 1.5-Tesla scanner with an 8-element phased array cardiac surface coil. CMR protocols included breath-hold steady state free precession cine, displacement encoded with simulated echoes (DENSE) and late gadolinium enhancement (LGE) phase sensitive inversion recovery (PSIR) (Payne et al 2011). Cine, DENSE and LGE CMR scans were obtained at the same position and only short-axis scans were post-processed in this study.…”
Section: Cmr Image Acquisitionmentioning
confidence: 99%
“…For example, in patients with a history of myocardial infarction, cardiac MRI can reveal infarct scar, haemorrhage and oedema, all of which can be linked with function. It has been shown [5,[26][27][28] that MRI is highly informative for assessing heart function, volumes and injury (area-at-risk, scar burden, salvaged myocardium, microvascular obstruction, haemorrhage and thrombus). In fact, infarct pathologies tend to aggregate in the highest risk patients in whom MRI is most informative.…”
Section: Introductionmentioning
confidence: 99%